Implementation of 6S in Convection MSME to Increase Worker Productivity - Putri, Febiola Andarista; Aurellia, Kamila; Priska, Hersa Ajeng; Zaidan, Ahmad; Basumerda, Chanchard (Proceeding International Conference on Religion, Science and Education, 2022)
In this time of economic growth, productivity becomes one of the main factors in competition in the manufacturing industry. Good performance and high efficiency are the keys for companies to be able to compete. The purpose of this study is to identify the layout of the facility and provide improvement recommendations. Analysis was conducted using the 6S Method (Sort, Set in order, Shine, Safety, Standardize, and Sustain) to find out the problems that occurred, manage the work area, increase efficiency, productivity and reduce the danger and risk of accidents in convection XYZ engaged in convection. The results of the 6S calculation show that the work area is currently in poor classification. The conclusion of this study is the design of the layout of the work area in convection and the provision of recommendations in the form of proposed improvements to provide closets and first aid tools in the work area.